Experimento de Galileu do plano inclinado em sala de aula - Santos, Max Luiz de Oliveira (Universidade Federal de São Carlos, 2014)
This work aims to make a suited reconstruction from the classic experiment of the inclined plane, attributed to Galileo Galilei. The intention is to apply it to high school classes, claiming that it might motivate these students to learn concepts related to physics, and should be able to better understand the subjective nature of what is behind the science and its construction process. It is intended to perform the experiment and guide the activities in order that the activities that students can better understand scientific knowledge as a result of human construction, as well as its inherent limitations, realizing that the science development is based on model making and experimentation, among others, which can be modified along the time. The discussion and investigation of the assumptions made by the great physicist, in the elaboration of the theory of falling bodies, and their validity, may result in rich discussions of scientific development. Students may discuss the possibility of adoption and acceptance of misconceptions in science, and what implications these have for the development of scientific theories. The work analyzes the measurement of time of ball bearings on the inclined plane, evaluating the primitive methods that Galileo could have used to reach its conclusions regarding this type of movement. The dissertation also approaches modern methods, as for example, the measurements of falling objects using a tape recorder of a microcomputer, and finally both time measurement procedures are discussing emphasizing historical and modern discussion of both forms, comparing historical and modern aspects in the development of science. Performed activities, finalize the work with the results of the project and its completion, prospects of continuity, assessing the feasibility of its use as an educational product that can serve as a tool in the process of teaching and learning in high school and used by other teachers in other contexts.
Keywords: Física - estudo e ensino; Galilei, Galileu, 1564-1642; Ciência - história; Galileo s experiment; History of science; Teaching of physics; CIENCIAS EXATAS E DA TERRA